2022
DOI: 10.2174/1573405617666211006122842
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lung Ultrasound Before and During the COVID-19 Pandemic: A Review Article

Abstract: : Lung ultrasound [LUS] has evolved considerably over the last years. The aim of the current review is to conduct a systematic review reported from a number of studies to show the usefulness of [LUS] and point of care ultrasound for diagnosing COVID-19. A systematic search of electronic data was conducted including the national library of medicine, and the national institute of medicine, PubMed Central [PMC] to identify the articles depended on [LUS] to monitor COVID-19. This review highlights the ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Common patterns described include irregular and thickened pleural line and multiple B-lines ranging from interstitial (three or more well-spaced B-lines) to compact (white lung), demonstrating interstitial to alveolointerstitial edema. Consolidation is found to be associated with the progression of the disease and its complications (10). LUS has shown a good correlation with computed tomography (11), so it was considered a valid tool during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Common patterns described include irregular and thickened pleural line and multiple B-lines ranging from interstitial (three or more well-spaced B-lines) to compact (white lung), demonstrating interstitial to alveolointerstitial edema. Consolidation is found to be associated with the progression of the disease and its complications (10). LUS has shown a good correlation with computed tomography (11), so it was considered a valid tool during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that LUS can be a promising technique for identifying COVID-19 and determining its outcome in hospitalized patients; similarly, a recent re- view article stated that LUS can help to detect and stage pulmonary involvement in COVID-19 pneumonia [29].…”
Section: Discussionmentioning
confidence: 53%
“…Our study suggested that LUS can be a promising technique for identifying COVID-19 and determining its outcome in hospitalized patients; similarly, a recent review article stated that LUS can help to detect and stage pulmonary involvement in COVID-19 pneumonia [ 29 ]. In another study, authors proposed a clinicoradiological scoring system and claimed that it may help to not only give a quantitative measure of lung involvement, but also to identify the probability of SARS-COV-2 pneumonia [ 30 ].…”
Section: Discussionmentioning
confidence: 78%